CO2 Emission Contribution Analysis of Rice Distribution Channels in Indonesia - Pratama, Armanda Redo (Sustainability (STPP) Theory, Practice and Policy, 2021)
According to Horrigan (2002), the food industry accounts for 10% of all fossil fuel consumption in the United States. Based on this, an effective rice distribution effort is needed as an effort to achieve food security. Moreover, the effective distribution channels will reduce the impact of CO2 emissions in the air. This study examines how the rice distribution channels in Indonesia and the amount of CO2 emissions resulting from these activities. This study using substitution analysis technique based on equation and conversion value of CO2 residue based on the type of transportation mode. The results show that the total emissions from rice distribution activities are 36.007,97 tons km or 0,026% of the total emissions generated by transportation activities